Współczesne media lokalne jako przedmiot refleksji medioznawczej - Kowalczyk, Ryszard (Wydział Nauk Politycznych i Dziennikarstwa UAM, 2011)
The paper concerns considerations on the areas of operation of modern local media in Po- land from the point of view of the paradigm of media studies. It outlines the evolution of the status of local media after 1989. It emphasizes the importance of the Round Table and the re- sulting political transformation in the process of restitution and development of local media in Poland. The paper also describes this segment of the media in terms of freedom and account- ability, market, economy and idea as well as social communication.
Modern Local Media as a Subject of Media Studies Reflection
Keywords: media lokalne; społeczna odpowiedzialność